Teaching geometry in basic education through digital technologies: A literature review (Research, Society and Development, 2025)
Geometry teaching has been transformed by the advancement of digital technologies, becoming more dynamic and interactive. The aim of this article is to analyze how these technologies have been integrated into Brazilian basic education, highlighting the use of resources that promote learning. The research, based on a bibliographic review of productions published between 2017 and 2025, identifies the use of tools such as GeoGebra, the Logo programming language and digital videos, exploring their contributions to the teaching and learning of geometric concepts. The results show that these resources facilitate the visualization and manipulation of figures, allowing students to understand concepts in a more concrete and participatory way. In addition, they promote the development of critical thinking, autonomy and collaboration, essential aspects for a meaningful mathematical education. However, for these resources to be used appropriately, it is essential that teachers are prepared to integrate technologies into their pedagogical practices. As Valente highlights, the adoption of digital tools must go beyond instrumental use, encouraging approaches that make the student the protagonist of their learning. Therefore, ongoing teacher training becomes essential to ensure the appropriate use of these technologies, aligned with the guidelines of the National Common Curricular Base and the needs of students.